(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The defence of provocation in Nigerian criminal law has long been burdened by an internal inconsistency: the requirement that a provoked person’s response must be proportionate to the provocation received. This doctrine, borrowed from English common law and consistently applied by Nigerian courts, demands rational restraint from an individual who, by the very definition of provocation, is said to have lost self-control and the mastery of his own mind. This study examines the jurisprudential foundation of the proportionality requirement and questions whether it can logically coexist with the core premise of the defence. Adopting a doctrinal legal research methodology, the paper analyses relevant Nigerian statutes (the Criminal Code and Penal Code), case law from the Supreme Court and lower courts, and comparative English authorities. The study finds that while the proportionality doctrine is firmly embedded in Nigerian judicial practice, neither the Criminal Code nor the Penal Code expressly incorporates it as an independent ingredient of the defence. Furthermore, the requirement creates a logical paradox: a person who has genuinely lost self-control cannot simultaneously be expected to measure the reasonableness of his response. Medical and psychological evidence on stress responses further undermines the doctrine’s assumptions. The paper concludes that proportionality should be reframed as one evidentiary factor among several, rather than a mandatory separate requirement. It recommends legislative reform to resolve this paradox and bring Nigerian criminal law into greater coherence with its own foundational principles.